The Sonic Hedgehog–Patched–Gli Signaling Pathway Maintains Dental Epithelial and Pulp Stem/Progenitor Cells and Regulates the Function of Odontoblasts - Ishikawa, Yuko; Ida-Yonemochi, Hiroko; Saito, Kotaro; Nakatomi, Mitsushiro; Ohshima, Hayato (Frontiers in Dental Medicine, 2021)
This study aimed to elucidate the role of the Sonic hedgehog (Shh)–Patched (Ptch)–Gli signaling pathway in maintaining dental epithelial and pulp stem/progenitor cells and regulating the function of odontoblasts. Doxycycline (dox)-inducible histone 2B (H2B)–green fluorescent protein (GFP) transgenic mice ingested dox at prenatal embryonic days 14.5 or 15.5 and their offspring were collected from postnatal day 1 (P1) to week 3 (P3W). Immunohistochemistry for Gli1, Ptch1, and Ptch2 and in situ hybridization for Shh and Ptch1 were conducted. Mandibular incisors of postnatal day 2 H2B-GFP transgenic and wild-type mice were cultivated in a nutrient medium with Shh antibody for 4 days and subsequently processed for immunohistochemistry for Sox2. In molars, dense H2B-GFP-label-retaining cells (H2B-GFP-LRCs) were densely distributed throughout the dental pulp during P1 to postnatal week 2 (P2W) and decreased in number by postnatal P3W, whereas the number of dense H2B-GFP-LRCs in the subodontoblastic layer increased in number at P2W. Gli1+ and Pthc1+ cells were distributed throughout the enamel organ and dental pulp, including the odontoblast and subodontoblastic layers. Shh mRNA was expressed in the inner enamel epithelium and shifted into odontoblasts after dentin deposition. Ptch1 mRNA was expressed in the inner enamel epithelium and cuspal pulpal tissue on P1 and decreased in intensity from postnatal week 1 to P3W. In incisors, the apical bud contained H2B-GFP-LRCs, Gli1+ cells, and Ptch1+ cells. The addition of Shh antibody to explants induced a decrease in the number of Sox2+ cells due to the increase in apoptotic cells in the apical bud. Thus, the Shh–Ptch–Gli signaling pathway plays a role in maintaining quiescent adult stem cells and regulating the function of odontoblasts.